Wisata Virtual Sebagai Sarana Pengenalan dan Pelestarian Budaya Di Tengah Pandemi (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2022)
The spread of Covid-19 has yet to subside. Many sectors of the economy were forced to stagnate due to the presence of Covid-19. In fact, according to data from the Ministry of Tourism and Creative Economy, the existence of large-scale social restrictions or commonly called PSBB and the closure of access to and from Indonesia, resulted in a significant decrease in state revenue, especially in the tourism sector by Rp20.7 billion. However, as the essence of humans as social beings, it is necessary to continue to be active, socialize, and fulfill needs. In this case, social change will always exist, as the view of Talcot Parson. Therefore, it is necessary as a human being to always be able to innovate to answer the challenges of the situation. Space restrictions due to the presence of a pandemic and the incessant development of technology make the topic of Virtual Tour so interesting for researchers. Then, the main discussion of this research is whether the presence of this Virtual Tour can replace the original function of offline tourism, which is still able to introduce and preserve culture to the community. then, this research is focused on using qualitative research and is supported by interview data and case studies. Through the results of interview data and case studies, this research then produces an answer that Virtual Tour is able to replace offline tourism functions. Where, Virtual Tour is able to be an alternative to introduce and preserve culture in the midst of a pandemic.Keywords: Virtual Tour, Tour, Pandemic.